Meningkatkan Mutu Pendidikan Islam di Madrasah Diniyah Babu Salam Blingoh Donorojo Jepara - Ashif Az Zafi; A'yun Qulubana Khusnan Arief; Eva Luthfi Fakhru Ahsani; Elya Umi Hanik (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2021)
Madrasah Diniyah is a non-formal Islamic educational institution. To become a pend institution. Islam requires high seriousness and motivation, high seriousness and motivation so that the goals and expectations of Madrasah Diniyah are achieved. Madrasas must continue to be an inspiration and motivation in minimizing the current moral crisis by instilling good morals in students through Islamic religious learning. This research is classified as a descriptive qualitative research conducted at Madrasah Diniyah Babus Salam Blingoh Donorojo Jepara. The purpose of this study was to find out how to improve the quality of education in Madrasah Diniyah Babus Salam. While the method of data collection using the method of observation and interviews. From the results of the study, it can be said that in improving the quality of Madrasah Diniyah education there are three elements, namely input, process, and output, but in its realization there are many obstacles in improving the quality of education in the field, namely social and economic problems.